Effects of Different Snow Clearing Measures on Urban Snowmelt Runoff Management - MA Zhenjie; FENG Youcan; TIAN Lin; GAO Jinhua; XUE Lijun (Renmin Zhujiang)
With the acceleration of urbanization and climate variability, urban disasters caused by rain, snow, and ice are becoming more consequential. In response to the issue of surface water accumulation due to snowmelt runoff in urban areas, the Storm Water Management Model (SWMM) is used to examine the influence of three kinds of snow clearing measures, i.e., mechanical, chemical, and manual measures, on the patterns of snowmelt runoff as well as the winter performance of low-impact development (LID) in cold regions. The findings indicate that the three snow clearing measures play a significant role in the regulation of urban surface runoff in cold regions, leading to an increase in surface runoff control rates ranging from 5.9% to 21.8%. Three types of snow clearing measures, in combination with LID applications, could all level up the surface runoff control rate to above 85%. This represents a 40.0%~44.2% improvement compared to scenarios without snow removal, a 22.4%~34.1% improvement compared to scenarios with only snow clearing measured applied, and a 1.5%~5.7% improvement compared to scenarios when the LID is applied alone. Therefore, snow clearing measures combined with LID can significantly improve the urban regulation of snowmelt runoff, and the effects of the various combinations of different types of snow-clearing measures and LID could be remarkably different.